Vancomycin‐Functionalized Porphyrinic Metal‐Organic Framework PCN‐224 with Enhanced Antibacterial Activity against Staphylococcus Aureus - Chen, Li‐Jian; Liu, Yao‐Yao; Zhao, Xu; Yan, Xiu‐Ping (Chemistry, an Asian journal, 2021)
A vancomycin (Van) modification strategy on a porphyrinic metal‐organic framework (MOF) PCN‐224 is presented. The obtained Van‐PCN‐224 gives the combined advantages of porphyrinic MOF and Van with high photosensitive activity and excellent targeted antibacterial activity against Staphylococcus aureus. The features make Van‐PCN‐224 promising for antimicrobial therapy. Vancomycin‐functionalized porphyrinic metal‐organic framework PCN‐224 displays the integrated merits of the bacteria‐targeting ability of vancomycin and the photodynamic effect of PCN‐224 for enhanced targeted sterilization.